Hubungan Resiliensi dengan Psychological Distress pada Masyarakat dalam Menghadapi Pandemi Covid-19 - Ismalandari Ismail; St Hadjar Nurul Istiqamah (Universitas Negeri Makassar, 2021)
This study aims to determined the relationship between resilience and psychological distress in the community in dealing with the Covid-19 pandemic. This type of research is a quantitative research using a questionnaire as a method of data collection. The measuring instrument used is a resilience scale, namely the Connor-Davidson Resilience Scale-10 and a psychological distress scale, namely the Kessler Psychological Distress Scale (K10). This study used a simple random technique in sampling. The number of subjects in this study amounted to 99 people. Data analysis was performed using Pearson's simple correlation technique. The results of the analysis of research data show that there is a negative relationship between resilience and psychological distress in the community in facing the Covid-19 pandemic. Individuals who have a high of resilience will experience low psychological distress. The correlation coefficient between resilience and psychological distress is -0.657 with p=0.000.